1998
DOI: 10.1029/98jc02370
|View full text |Cite
|
Sign up to set email alerts
|

The development and operational application of nonlinear algorithms for the measurement of sea surface temperatures with the NOAA polar‐orbiting environmental satellites

Abstract: Abstract. Since 1990, the NOAA National Environmental Satellite Data and Information Service (NESDIS) has provided satellite-derived sea surface temperature (SST) measurements based on nonlinear SST algorithms, using advanced very high resolution radiometer (AVHRR) multiple-infrared window channel data. This paper develops linear and nonlinear SST algorithms from the radiative transfer equation. It is shown that the nonlinear algorithms are more accurate than linear algorithms but that the functional dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
234
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(241 citation statements)
references
References 32 publications
3
234
1
3
Order By: Relevance
“…Korean Journal of Remote Sensing, Vol.27, No.6, 2011 -672- MCSST algorithm without any significant improvement in the study region, which was contrast with the previous researches concerning its improved accuracy (Walton, 1988;Walton et al, 1998).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Korean Journal of Remote Sensing, Vol.27, No.6, 2011 -672- MCSST algorithm without any significant improvement in the study region, which was contrast with the previous researches concerning its improved accuracy (Walton, 1988;Walton et al, 1998).…”
Section: Discussioncontrasting
confidence: 52%
“…This may be partly related to difficulty to eliminate cloudcontaminated pixels because of unavailability of visible channel data at night. NLSST algorithm was evaluated to be slightly more accurate than MCSST algorithm as presumed from the rms errors in Table 4, but no significant improvement unlike the previous literature (e.g., Walton et al, 1998). Although NOAA-19 matchups could not include the first half of 2009, the errors satisfied the reasonable limit of less than 1˚C.…”
Section: ) Accuracies Of Sstsmentioning
confidence: 74%
See 2 more Smart Citations
“…Results from several studies (e.g. Li et al, 2001;Oesch et al, 2005) have shown that the linear version of the multi-channel splitwindow equation gives slightly better results (lower biases) than the non-linear equation of Walton et al (1998). Thus, we use similar to Hulley et al (2011) the linear multi-channel equation…”
Section: Split-window Approachmentioning
confidence: 99%